Rural Communities Development in Ukraine in Times of COVID-19 Pandemic: Socio-Economic Aspects - Aleksandra SYNOWIEC (Communications of International Proceedings, 2021)
The author discusses the issues of rural communities development in Ukraine in the context of the COVID-19 pandemic. The purpose of this paper is to identify and discuss the socio-economic problems rural communities face on account of the COVID-19 aftermath.  Studies show that residents of rural areas in continuously experience various forms of discrimination in the spheres of employment, education, healthcare or decision-making process. The main question is in what way the introduction of epidemic restrictions affects socio-economic performance of rural dwellers in Ukraine. The analysis is based on available secondary data, which consists of selected literature on the subject of rural development in Ukraine, available reports and studies of international institutions, research agencies, state documents and statistics, research conducted by international and domestic NGO’s. The course of study involves recognition of barriers and drivers of sustainable development as well as identification of the core factors of the COVID-19 impact on rural dwellers life.   Social groups particularly affected due to the global pandemic crisis and undertaken countermeasures  were recognized and spheres of social inequalities were indicated. It was also noted how the pandemic can contribute to the development of rural areas.
Keywords: Rural Communities; Rural Development; COVID-19 Impact; Sustainability